TCPSD Process Control for Separation of Acetonitrile/Benzene/Methanol Mixture (Research, Society and Development, 2022)
Aiming for greater saving on operating costs, the inclusion of recycle streams and thermal integrations are routine in chemical processes, generating need for more robust control structures capable of preventing losses due to routine disturbances and providing operational safety. The Triple-Column-Pressure-Swing-Distillation (TCPSD) separation can be used to separate different solvents from the fine chemical industry, and due to the large number of variables involved, together with thermal integrations and recycle streams, the definition of an effective control structure becomes a complex problem. At this context, this paper has as main objective the development and evaluation of plantwide control structures for a TCPSD process used to separate the acetonitrile/benzene/methanol mixture. Using the Aspen Plus© and Aspen Plus Dynamics© software, two control structures were evaluated, in which the product compositions are controlled by inference, by controlling the temperature of sensitive plates. The main difference between the two structures is that Control Structure 1 has a dual sum control loop of temperature sensitive plates in the low-pressure column, manipulating the reflux ratio. When evaluating the results of compositions of products when reaching steady state and ISE values, it was concluded that both structures are capable of controlling step-type disturbances in flow and composition at feed stream of the process. However, the better results were observed in Control Structure 1.